Bisphosphonate-Related Osteonecrosis of the Jaw: A Review of the Literature - Eder Alberto Sigua-Rodriguez; Renato da Costa Ribeiro; Ana Caroline Ramos de Brito; Natalia Alvarez-Pinzon; José Ricardo de Albergaria-Barbosa (International Journal of Dentistry)
Bisphosphonates (BPs) are a class of drugs used to treat osteoporosis and malignant bone metastasis. BPs show high binding capacity to the bone matrix, especially in sites of active bone metabolism. The American Society for Bone and Mineral Research defines BRONJ as “an area of exposed bone in the maxillofacial region that has not healed within 8 weeks after identification by a healthcare provider in a patient who is receiving or has been exposed to a bisphosphonate and has not had radiation therapy to the craniofacial region.” Bisphosphonate-related osteonecrosis of the jaw (BRONJ) can adversely affect quality of life, as it may produce significant morbidity. The American Association of Oral and Maxillofacial Surgeons (AAOMS) considers as vitally important that information on BRONJ be disseminated to other dental and medical specialties. The purpose of this work is to offer a perspective on how dentists should manage patients on BPs, to show the benefits of accurately diagnosing BRONJ, and to present diagnostic aids and treatments strategies for the condition.